Answer:
Y=-5/3x
Step-by-step explanation:
Use the slope formula and slope-intercept form y=mx+b to find the equation.
Answer:
- 10√2 - 5√5
Step-by-step explanation:
- 2√50
√50 = √( 2 x 5 x 5 ) = 5√2
- 2√50
= - 2 x 5√2
= - 10√2
- √125
= - √( 5 x 5 x 5 )
= - 5√5
- 2√50 - √125
= - 10√2 - 5√5
There are two ways to do this.
The first way is to algebraically find (f+g)(x) first and plug in x = 5 later. Doing that method leads us to
(f+g)(x) = f(x) + g(x)
(f+g)(x) = 6x+3 + x-4
(f+g)(x) = 7x-1
(f+g)(5) = 7(5)-1
(f+g)(5) = 34
OR
you can compute f(5) and g(5) first, then add up those sub-results to get
f(x) = 6x+3
f(5) = 6(5)+3
f(5) = 33
g(x) = x-4
g(5) = 5-4
g(5) = 1
Adding up these results gives: (f+g)(5) = f(5) + g(5) = 33+1 = 34
Either way, the final answer is 34
Answer:
x = 2√13.
Step-by-step explanation:
Using the Pythagoras theorem:
14^2 = x^2 + 12^2
x^2 = 14^2 - 12^2
x^2 = (14 + 12)(14 - 12) = 52
x = √52
x = √4*√13
x = 2√13.